Receipt of recommended complications and comorbidities screening in youth and young adults with type 1 diabetes: Associations with metabolic status and satisfaction with care. Issue 2 (16th December 2019) - Malik, Faisal S.; Stafford, Jeanette M.; Reboussin, Beth A.; Klingensmith, Georgeanna J.; Dabelea, Dana; Lawrence, Jean M.; Mayer‐Davis, Elizabeth; Saydah, Sharon; Corathers, Sarah; Pihoker, Catherine; ,
Abstract: Objectives: This study sought to: (a) assess the prevalence of diabetes complications and comorbidities screening as recommended by the American Diabetes Association (ADA) for youth and young adults (YYAs) with type 1 diabetes (T1D), (b) examine the association of previously measured metabolic status related to diabetes complications with receipt of recommended clinical screening, and (c) examine the association of satisfaction with diabetes care with receipt of recommended clinical screening. Methods: The study included 2172 SEARCH for Diabetes in Youth participants with T1D (>10 years old, diabetes duration >5 years). Mean participant age was 17.7 ± 4.3 years with a diabetes duration of 8.1 ± 1.9 years. Linear and multinomial regression models were used to evaluate associations. Results: Sixty percent of participants reported having three or more hemoglobin A1c (HbA1c) measurements in the past year. In terms of diabetes complications screening, 93% reported having blood pressure measured, 81% having an eye examination, 71% having lipid levels checked, 64% having a foot exam, and 63% completing albuminuria screening in accordance with ADA recommendations. Youth known to have worse glycemic control in the past had higher odds of not meeting HbA1c screening criteria (OR 1.11, 95% CI = 1.05, 1.17); however, after adjusting for race/ethnicity, this was no longer statistically significant. Greater satisfaction with diabetes care was associated with increased odds of meeting screening criteria for most of the ADA‐recommended measures. Conclusions: Efforts should be made to improve diabetes complications screening efforts for YYAs with T1D, particularly for those at higher risk for diabetes complications.